Implementasi Konsep Pariwisata SPA Halal pada Salon dan SPA di Kota Padang - Prilly Azhari Rizqa; Tyas Asih Surya Mentari (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
This study discusses the implementation of the halal SPA tourism concept in salons and SPAs in Padang City, amidst the growing halal tourism sector that emphasizes Islamic values. The purpose of this research is to describe the application of product, service, and management aspects based on halal standards. A descriptive qualitative approach was used, employing observation, interviews, and documentation methods across 10 salons and SPAs. Data were analyzed through reduction, presentation, and conclusion techniques. The results show that most salons and SPAs have begun to implement the halal tourism concept, including separate treatment rooms, the use of certified halal products, and the provision of prayer facilities. Muslimah Beauty Care stands out with its Islamic prayer books and magazines, while OK SPA and Beauty Lounge have adopted Islamic SOPs, including greetings and prayers. However, there are still inconsistencies in implementation, particularly in uniformity of Islamic dress for staff and product halal certification. Overall, salons and SPAs in Padang are making efforts to follow the halal tourism concept but require improvement in implementation to meet optimal standards.